Alternative parameters for echocardiographic assessment of fetal diastolic function - Zielinsky,P. (2004)
Alternative methods to assess ventricular diastolic function in the fetus are proposed. Fetal myocardial hypertrophy in maternal diabetes was used as a model of decreased left ventricular compliance (LVC), and fetal respiratory movements as a model of increased LVC. Comparison of three groups of fetuses showed that, in 10 fetuses of diabetic mothers (FDM) with septal hypertrophy (SH), the mean excursion index of the septum primum (EISP) (ratio between the linear excursion of the flap valve and the left atrial diameter) was 0.36 ± 0.09, in 8 FDM without SH it was 0.51 ± 0.09 (P = 0.001), and in the 8 normal control fetuses (NCF) it was 0.49 ± 0.12 (P = 0.003). In another study, 28 fetuses in apnea had a mean EISP of 0.39 ± 0.05 which increased to 0.57 ± 0.07 during respiration (P < 0.001). These two studies showed that the mobility of the septum primum was reduced when LVC was decreased and was increased when LVC was enhanced. Mean pulmonary vein pulsatility was higher in 14 FDM (1.83 ± 1.21) than in 26 NCF (1.02 ± 0.31; P = 0.02). In the same fetuses, mean left atrial shortening was decreased (0.40 ± 0.11) in relation to NCF (0.51 ± 0.09; P = 0.011). These results suggest that FDM may have a higher preload than normal controls, probably as a result of increased myocardial mass and LV hypertrophy. Prenatal assessment of LV diastolic function by fetal echocardiography should include analysis of septum primum mobility, pulmonary vein pulsatility, and left atrial shortening.